Mycobacterium tuberculosis population structure and molecular epidemiological analysis in Sucre municipality, Miranda state, Venezuela. - Patiño, Margareth; Abadía, Edgar; Gómez, Solalba; Maes, Mailis; Muñoz, Mariana; Gómez, Daniela; Guzmán, Patricia; Méndez, María Victoria; Ramirez, Carmen; España, Mercedes; de Waard, Jacobus; Takiff, Howard (Investigación Clínica, 2014)
Sucre municipality is a large, densely populated marginal area in the eastern part of Caracas, Venezuela that consistently has more cases of tuberculosis than other municipalities in the country. To identify the neighborhoods in the municipality with the highest prevalence of tuberculosis, and determine whether the Mycobacterium tuberculosis strain distribution in this municipality is different from that previously found in the western part of Caracas and the rest of Venezuela, we collected data on all tuberculosis cases in the municipality diagnosed in 2005-6. We performed two separate molecular epidemiological studies, spoligotyping 44 strains in a first study, and spoligotyping 131 strains, followed by MIRU-VNTR 15 on 21 clustered isolates in the second. With spoligotyping, the most common patterns were Shared International Type SIT17 (21%); SIT42 (15%); SIT93 (11%); SIT20 (7%); SIT53 (6%), a distribution similar to other parts of Venezuela, except that SIT42 and SIT20 were more common. MIRU-VNTR 15 showed that six of seven SIT17 strains examined belonged to a large cluster previously found circulating in Venezuela, but all of the SIT42 strains were related to a cluster centered in the neighborhoods of Unión and Maca, with a MIRU-VNTR pattern not previously seen in Venezuela. It appears that a large percentage of the tuberculosis in the Sucre municipality is caused by the active transmission of two strain families centered within distinct neighborhoods, one reflecting communication with the rest of the country, and the other suggesting the insular, isolated nature of some sectors.